2016
DOI: 10.1021/acs.joc.6b02294
|View full text |Cite
|
Sign up to set email alerts
|

N-Acylsaccharins as Amide-Based Arylating Reagents via Chemoselective N–C Cleavage: Pd-Catalyzed Decarbonylative Heck Reaction

Abstract: Palladium-catalyzed decarbonylative Heck reaction of amides by chemoselective N-C activation using N-acylsaccharins as coupling partners has been accomplished. These studies represent only the second example of amide-Heck reactions reported to date. A broad range of electronically diverse amide and olefin coupling partners is amenable to this transformation. Orthogonal site-selective Heck cross-couplings by C-Br/N-C cleavage and mechanistic studies are reported. This report introduces readily available, bench-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 65 publications
(43 reference statements)
1
36
0
Order By: Relevance
“…The palladium-catalyzedd ecarbonylative Heck cross-coupling reactiono fN-acylsaccharins with olefins through amide NÀCa ctivation was reported by Szostak and co-workers (Scheme 12). [47] They chose N-acylsaccharins as the coupling partner because it was air-stable, cheap,a nd widely available. Their method was operationally simple, base-free, and ligandfree and toleratedawide variety of functional groups.…”
Section: Cross-coupling and Other Reactionsmentioning
confidence: 99%
“…The palladium-catalyzedd ecarbonylative Heck cross-coupling reactiono fN-acylsaccharins with olefins through amide NÀCa ctivation was reported by Szostak and co-workers (Scheme 12). [47] They chose N-acylsaccharins as the coupling partner because it was air-stable, cheap,a nd widely available. Their method was operationally simple, base-free, and ligandfree and toleratedawide variety of functional groups.…”
Section: Cross-coupling and Other Reactionsmentioning
confidence: 99%
“…A wide range of aryl, heteroaryl and alkenyl N ‐glutarimide amides reacted efficiently with diverse olefins to give the desired products in good yields (65–94 %) as well as excellent stereoselectivity ( E / Z >98:2 in all cases) and regioselectivity (linear product favored). The same group recently further demonstrated that N ‐acylsaccharins are also applicable in the Pd‐catalyzed decarbonylative Heck reactions …”
Section: Carbon–carbon Bond Forming Reactionsmentioning
confidence: 99%
“…The same group recently further demonstrated that N-acylsaccharins are also applicable in the Pd-catalyzedd ecarbonylative Heck reactions. [25] Scheme13. Ni-catalyzed decarbonylative alkylation reaction of carboxylic esters with organozinc compounds.…”
Section: Mizoroki-heck-type Reactionmentioning
confidence: 99%
“…[17][18][19][20] Traditional syntheses of this substructure, such as Wittig or Julia olefinations, [21,22] Pd-catalyzed Heck-type coupling [23][24][25][26][27] and some reduction and condensation methods using suitable substrates, [28][29][30] are waste-intensive, limited in scope and/or require multistep syntheses of starting materials. (E)-1,2-Diarylethene scaffolds have received a great deal of attention from biology and synthetic chemistry researchers in the past decade because of their wide-ranging spectrum of biological activities and broad applications in various fields of research.…”
Section: Introductionmentioning
confidence: 99%